Novel Role of Endogenous Catalase in Macrophage Polarization in Adipose Tissue - Ye Seul Park; Md Jamal Uddin; Lingjuan Piao; Inah Hwang; Jung Hwa Lee; Hunjoo Ha (Mediators of Inflammation)
Macrophages are important components of adipose tissue inflammation, which results in metabolic diseases such as insulin resistance. Notably, obesity induces a proinflammatory phenotypic switch in adipose tissue macrophages, and oxidative stress facilitates this switch. Thus, we examined the role of endogenous catalase, a key regulator of oxidative stress, in the activity of adipose tissue macrophages in obese mice. Catalase knockout (CKO) exacerbated insulin resistance, amplified oxidative stress, and accelerated macrophage infiltration into epididymal white adipose tissue in mice on normal or high-fat diet. Interestingly, catalase deficiency also enhanced classical macrophage activation (M1) and inflammation but suppressed alternative activation (M2) regardless of diet. Similarly, pharmacological inhibition of catalase activity using 3-aminotriazole induced the same phenotypic switch and inflammatory response in RAW264.7 macrophages. Finally, the same phenotypic switch and inflammatory responses were observed in primary bone marrow-derived macrophages from CKO mice. Taken together, the data indicate that endogenous catalase regulates the polarization of adipose tissue macrophages and thereby inhibits inflammation and insulin resistance.